The fragmentation of 20Ne at 400 A MeV - 程锦霞 张东海 晏世伟 李俊生 王立春 李彦晶 N. Yasuda (Chinese physics C, 2012)
The total charge-changing cross sections and partial cross sections for the production of projectile fragments are measured in the interactions of 400 A MeV 20 Ne with aluminum,carbon and polyethylene targets sandwiched with CR-39 plastic nuclear track detectors.The measured total charge-changing cross sections are compared with the predictions using the Bradt-Peters semi-empirical formula,and the NUCFRAG2 and PHITS models.It is shown that the measured experimental results are in good agreement with the theoretical model prediction and other experimental results,and it can be clearly seen that the partial cross sections for fragment production show obvious odd-even effects.